Pengaruh Pembelajaran Akuntansi Keuangan, Literasi Keuangan, Locus Of Control, Gaya Hidup, dan Financial Technology Terhadap Perilaku Keuangan Mahasiswa Akuntansi Universitas Kristen Duta Wacana - Wella; Setyani, Astuti Yuli (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of financial accounting learning, financial literacy, locus of control, lifestyle, and financial technology on the financial behavior of Accounting Study Program students at Duta Wacana Christian University. The theoretical framework is based on the Theory of Planned Behavior (Ajzen, 1991), which explains that behavior is influenced by intention, attitude, subjective norms, and perceived behavioral control. This research employs a quantitative approach with a correlational method. Primary data were collected through questionnaires distributed to 135 respondents and analyzed using multiple linear regression with SPSS software. The results indicate that financial accounting learning, locus of control, and financial technology have a positive effect on students’ financial behavior, while financial literacy and lifestyle show no effect. Simultaneously, all five independent variables affect students’ financial behavior. These findings emphasize the importance of accounting education, self-control, and the wise use of financial technology in shaping healthy financial behavior among students.